Correction: Global Analysis of the Human Pathophenotypic Similarity Gene Network Merges Disease Module Components. - Armando Reyes-Palomares; Rocío Rodríguez-López; Juan A G Ranea; Francisca Sánchez-Jiménez; Miguel Angel Medina (PLoS ONE, 2013)
[This corrects the article on p. e56653 in vol. 8.].